Revision surgery versus biologic treatment with omalizumab in recurrent chronic rhinosinusitis with nasal polyps: An analysis of cost-utility and clinical outcomes - Yutong Sima, MS; Jing Zhang, MS; Ming Zheng, MD; Yan Zhao, PhD; Xiangdong Wang, MD, PhD; Luo Zhang, MD, PhD (World Allergy Organization Journal, 2023)
Background: Both revision surgery and omalizumab are recommended therapies for the treatment of recurrent chronic rhinosinusitis with nasal polyps (CRSwNP) and can improve patients' clinical symptoms and quality of life (QoL). The aim of this study was to compare the improvement in sinus-related symptoms, QoL, economic cost, and duration cost between treatment with revision-surgery and treatment with omalizumab. Methods: This was a prospective study of patients with recurrent CRSwNP. All patients were asked to complete a 22-item sino-nasal outcome test (SNOT-22), a visual analog scale (VAS), and a 36-item short-form (SF-36) questionnaire at baseline and 6 months after the treatments. Patients were required to document economic costs and duration costs within 6 months and report them at each visit. Results: A total of 44 patients who received the treatment of revision surgery or omalizumab were enrolled in this study. After six months of treatment, the improvements in total SNOT-22 and SF-36 in 8 domains were not different between the 2 treatments. The improvements in rhinologic symptoms, extranasal rhinologic symptoms, and ear/facial symptoms according to the SNOT-22 (P value = 0.0288, 0.0016, and 0.0347, respectively) and the improvements in nasal congestion, loss of smell, and overall symptoms assessed by the VAS (P value = 0.0057, 0.0206, and 0.0122, respectively) were better in the revision surgery group than in the omalizumab group. The economic cost and the total duration cost were obviously lower in the omalizumab group (¥18836 and 1 day) than in the revision surgery group (¥29824 and 23 days). Conclusions: Both revision surgery and omalizumab treatments can improve the clinical symptoms and QoL of patients with recurrent CRSwNP. Patients who underwent revision surgery experienced better improvement in sinus-related symptoms. However, omalizumab treatment clearly showed a benefit in terms of economic cost and duration cost of disease-related care.